Analysis of algal cell elements collected from temple tanks, rock ponds and seashore in Kovalam and Mahabalipuram, Tamil Nadu, India - Barthelomai Infant Santhose, Natesan Senthil Kumar, Ramasamy Sakthivel, Sanniyasi Elumalai*, (International Multidisciplinary Research Journal, 2011)
Four species of micro and macroalgae collected from Mahabalipuram and Kovalam were analyzed for their elemental composition with the help of Perkin Elmer Optima DV Inductively Couple Plasma – Optical Emission Spectroscopy. Several significant elements e.g., Calcium, Magnesium, Sodium, Potassium and Iron were detected quantitatively. Calcium, Potassium, Magnesium were found in large amounts (22.461 – 626.385 ppm), Iron and Sodium were present in small quantities (2.391 – 6.167 ppm). The average quantity of Potassium was found to be highest among these algae (626.385 ppm), followed by Calcium (65.253 ppm) and Magnesium (22.461 ppm) and low quantity of Sodium (6.167 ppm) and Iron (2.391 ppm).